THE EFFECT OF LONG SOAKING BALI BEEF WITH LETTUCE FERMENTED SOLUTION (Lactuca sativa) ON PHYSICAL QUALITY AND TOTAL LACTIC ACID BACTERIA - K. S. S., Panjaitan; Lindawati, S. A.; Miwada, I N. S. (Jurnal Peternakan Tropika; Vol 10 No 1 (2022): Vol. 10 No. 1 Tahun 2022; January - april, 2022)
Meat is a food of animal origin that is easily damaged due to the activity of food-destroying microorganisms. Lettuce solution ( Lactuca sativa ) is an alternative natural preservative because there are lactic acid bacteria in it. This study aims to determine that the duration of soaking Bali beef with lettuce fermented solution ( Lactuca sativa ) effects the physical quality and total lactic acid bacteria.  This research was conducted in April to June 2021 at the Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Husbandry, Udayana University. The study was conducted using a completely randomized design (CRD) with four treatments and four replications. The four treatments were: without soaking with lettuce fementation solution (P0), soaking with lettuce fermentation solution for 30 minutes (P1), soaking with lettuce fermentation solution for 60 minutes (P2), soaking with lettuce fermentation solution for 90 minutes (P3). The variables observed were the physical quality of the meat which included pH, color, water holding capacity, cooking and raw shrinkage and total Lactic Acid Bacteria (LAB). The results showed that soaked beef using lettuce fermentation solution obtained pH 5.95-5.97; water holding capacity 25.11% - 26.15%; cooking loss 42.06% - 40.74%; raw shrinkage 9.29% - 8.12%; color 4.25% - 5.25%'; lactic acid bacteria 3.8 x 10 5 – 2.7 x 10 5 CFU/g. Based on the results of the study, it can be concluded that the soaking time of 30, 60 and 90 minutes of Balinese beef with lettuce fermentation solution ( Lactuca sativa ) did not affect the pH value, water holding capacity, cooking loss, raw shrinkage, color and total lactic acid bacteria, but it affects the shrinkage of raw meat and the soaking time of 60 minutes of Balinese beef with lettuce fermented solution had good physical quality. Keywords: Beef, lettuce fermentation, physical quality, total lactic acid bacteria